La construction de l’image du corps de l’élite égyptienne à l’époque amarnienne - Cathie Spieser; Pierre Sprumont (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Several diseases were hypothetized to explain the uncommon aspect of Akhenaten in his artistic representations, without taking in consideration the stylistic, historical, anthropological and medical data, which, in turn, allowed to contradict them. The most recent of these hypotheses concerned the Marfan syndrome. There are indeed some indications that the king suffered from hyperlaxity of the ligaments, a symptom frequently encountered in the Marfan symptomatology, but also existing as an isolated form. The authors also examined the various hypotheses made about the elongated skulls present in the sculptured heads of the princesses. The shape complexity going from stylisation to personalisation including some degree of anatomical realism was analysed and evaluated. Based upon several marks present on the sculptures, the authors do not exclude the possibility of a deformation practice operated on the persons having served as models. They also take into account the anthropological elements available, including the skulls of Smenkhkare and Tutankhamun. They eventually mention the ideological and theological context surrounding these representations.